PENGARUH UKURAN PERUSAHAAN, LEVERAGE, SALES GROWTH, PROFITABILITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Erna Diyastuti; Nur Kholis (PROSEDING, 2022)
Tax avoidance is a strategy and technique in avoiding taxation that is carried out legally and has security for taxpayers, because it does not conflict with policies regarding taxes. The purpose of the following research is to understand the effect of Company Size, Leverage, Sales Growth and Profitability on Tax Avoidance in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The sample used is 11 companies in the pharmaceutical sector from 2019 to 2021, so 31 data are obtained that are used for samples of research implementation. The source of data in this study was obtained from the website (www.idx.co.id). The implementation of the following research uses a multiple linear regression model using SPSS 19 to analyze the effect of the independent variables on the dependent variable used in the research implementation. The results of the following research activities indicate that firm size and profitability have an influence on efforts to avoid tax or tax avoidance. Meanwhile, leverage and sales growth have no effect on tax avoidance. Keywords: Company Size, Leverage, Sales Growth, Profitability, Tax Avoidance.